2019
DOI: 10.5194/hess-23-3405-2019
|View full text |Cite
|
Sign up to set email alerts
|

Improving hydrological projection performance under contrasting climatic conditions using spatial coherence through a hierarchical Bayesian regression framework

Abstract: Abstract. Understanding the projection performance of hydrological models under contrasting climatic conditions supports robust decision making, which highlights the need to adopt time-varying parameters in hydrological modeling to reduce performance degradation. Many existing studies model the time-varying parameters as functions of physically based covariates; however, a major challenge remains in finding effective information to control the large uncertainties that are linked to the additional parameters wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…Thus, the 211 method proposed by Saft et al (2015) was introduced in this study to define the meteorological 212 drought period. A more detailed process of the identification method of dry period can be obtained 213 in research by Saft et al (2015) and our previous study (Pan et al, 2019b). water storage capacity, is the most sensitive parameter in the structure of the GR4J model.…”
Section: Identification Of Meteorological Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the 211 method proposed by Saft et al (2015) was introduced in this study to define the meteorological 212 drought period. A more detailed process of the identification method of dry period can be obtained 213 in research by Saft et al (2015) and our previous study (Pan et al, 2019b). water storage capacity, is the most sensitive parameter in the structure of the GR4J model.…”
Section: Identification Of Meteorological Droughtmentioning
confidence: 99%
“…Furthermore, recent literature indicates that the improved probabilities of the extreme events 60 have been projected in many parts around the world because of the increasing anthropogenic 61 interference and global climate change, which implies the more severe droughts in the future (Dai,62 2012; Dai, 2011;Pan et al, 2019b). Unlike other natural hazards, e.g., flood, cyclonic storms and 63 earthquakes, the drought may have a much longer duration.…”
mentioning
confidence: 99%
“…For instance, significant variations (i.e., less runoff than expected) in hydrological behaviour were reported during the decade-long millennium drought of many catchments in south-eastern Australia compared with the previous wet period (Saft et al, 2016). Seasonally asymptotic variation have been identified in many catchments in America (Deng et al, 2018;Pan et al, 2019a), Asia (Deng et al, 2016) and Australia (Pan et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…through certain criteria. Thus, the functional form that achieved the best simulation performance would be recognized as the best item to represent the potential changes in the catchment property (Jeremiah et al, 2013;Westra et al, 2014;Wright et al, 2015;Guo et al, 2017;Pan et al, 2019a;Pan et al, 2019b). For example, Westra et al (2014) found that the streamflow prediction of the Scott Creek catchment in South Australia was significantly improved if the CWSC is allowed to change over time as a combined function.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research conducted by Guillaume is of great significance in dealing with the impact of land-use transformation on a wide range of potential ecologies [19]. Generally speaking, it is clear from the literature that global climate change and human activities are the two main factors affecting LUCC [20]. Deepening the analysis of the temporal and spatial evolution and driving factors of land use can improve our understanding of sustainable development and help us better examine the relationship between people and land use.…”
Section: Introductionmentioning
confidence: 99%